2017
DOI: 10.1186/s12917-017-1149-6
|View full text |Cite
|
Sign up to set email alerts
|

Botanical ethnoveterinary therapies used by agro-pastoralists of Fafan zone, Eastern Ethiopia

Abstract: BackgroundIn Ethiopia, plant based remedies are still the most important and sometimes the only source of therapeutics in the management of livestock diseases. However, documentation of this indigenous knowledge of therapeutic system still remains at a minimum level. The aim of this study was, thus, to document the traditional knowledge of botanical ethnoveterinary therapies in the agro-pastoral communities of Fafan Zone, Eastern Ethiopia.MethodsThe study employed a cross-sectional participatory survey. Purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
7
18
0
Order By: Relevance
“…The majorly treated livestock ailments of this study were supported by number of documents [19, 20, 29, 34]. However, this result is in contrast with [18, 27] which indicate the majorly treated livestock ailments are diarrhea and wound rather than black leg. The in agreement might be due to the prevalence rate of most livestock ailments from different agroecology oblige healers and respondents to focus on frequently occurring ailment with long years of experience in treatment.…”
Section: Resultsmentioning
confidence: 46%
“…The majorly treated livestock ailments of this study were supported by number of documents [19, 20, 29, 34]. However, this result is in contrast with [18, 27] which indicate the majorly treated livestock ailments are diarrhea and wound rather than black leg. The in agreement might be due to the prevalence rate of most livestock ailments from different agroecology oblige healers and respondents to focus on frequently occurring ailment with long years of experience in treatment.…”
Section: Resultsmentioning
confidence: 46%
“…C. quadrangularis is claimed to be used in livestock against helminthiasis, tick and lice infestation, and leach infestation. Similarly, S. molle is widely used by pastoralists and agropastoralists of Ethiopia to eradicate intestinal parasites [ 13 , 14 ]. Therefore, it was found necessary to evaluate the anthelmintic potential of two of the commonly used herbs by the pastoralist communities of Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The use of herbal extracts or the traditional ethno-veterinary medicinal practices in the treatment of various veterinary diseases in developing countries is well known; however, the reports of ethno-veterinary medicinal practices in treatment of bovine mastitis is lesser known and reported. Feyera et al (2017) reported that botanical ethnoveterinary therapies are the mainstay of livestock health care system in Fafan Zone, Eastern Ethiopia. Aziz et al (2018) investigated 73 medicinal plants used by indigenous communities for veterinary practices in Pakistan.…”
Section: Discussionmentioning
confidence: 99%